2012
DOI: 10.1038/bcj.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

The oral HDAC inhibitor pracinostat (SB939) is efficacious and synergistic with the JAK2 inhibitor pacritinib (SB1518) in preclinical models of AML

Abstract: Acute myeloid leukemia (AML) is currently treated with aggressive chemotherapy that is not well tolerated in many elderly patients, hence the unmet medical need for effective therapies with less toxicity and better tolerability. Inhibitors of FMS-like tyrosine kinase 3 (FLT3), JAK2 and histone deacetylase inhibitors (HDACi) have been tested in clinical studies, but showed only moderate single-agent activity. High efficacy of the HDACi pracinostat treating AML and synergy with the JAK2/FLT3 inhibitor pacritinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…In fact, preclinical studies suggest that JAK inhibitors synergize with bcl-2 inhibitors both in MPNs and lymphoma in in vitro and in vivo models [93,94]. Synergism with MEK and histone deacetylase (HDAC) inhibitors has been also reported in in vitro HL models and MPNs, respectively [73,95,96]. On the other hand, the GI toxicity observed [79,80] Phase II (MPNs) -JAK2, JAK1, JAK3 JNK, CDK2 Thrombocytopenia, transaminasemia, hyperlipase/amylasemia, neuropathy LY2784544 [81] Phase I/II (MPNs) -Selective JAK2V617F Nausea, diarrhea, anemia, increased creatinine XL019 [82] Stopped (MPNs) -JAK2, JAK1, JAK3 Peripheral neuropathy BMS911543 [84] Phase I/II (MPNs) -JAK2 NA NS-018 [83] Phase I/II ( …”
Section: Resultsmentioning
confidence: 99%
“…In fact, preclinical studies suggest that JAK inhibitors synergize with bcl-2 inhibitors both in MPNs and lymphoma in in vitro and in vivo models [93,94]. Synergism with MEK and histone deacetylase (HDAC) inhibitors has been also reported in in vitro HL models and MPNs, respectively [73,95,96]. On the other hand, the GI toxicity observed [79,80] Phase II (MPNs) -JAK2, JAK1, JAK3 JNK, CDK2 Thrombocytopenia, transaminasemia, hyperlipase/amylasemia, neuropathy LY2784544 [81] Phase I/II (MPNs) -Selective JAK2V617F Nausea, diarrhea, anemia, increased creatinine XL019 [82] Stopped (MPNs) -JAK2, JAK1, JAK3 Peripheral neuropathy BMS911543 [84] Phase I/II (MPNs) -JAK2 NA NS-018 [83] Phase I/II ( …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies with JAK2 V617F -mutant cells showed that pan-deacetylase inhibition enhanced suppression of JAK/STAT signaling by a JAK2 inhibitor, and the combination exerted synergistic apoptosis induction (16). Finally, in JAK2-or FLT3-mutant acute myelogenous leukemia (AML) xenograft models, the HDAC inhibitor pracinostat displayed synergistic tumor growth inhibition in combination with the dual JAK2/FLT3 inhibitor pacritinib (31).…”
Section: Discussionmentioning
confidence: 99%
“…Pracinostat as single agent reduced the plasma MCP-1 level by 40% while 10% reduction was seen upon pacritinib treatment. The combined treatment reduced the defined cytokine plasma level by 69% or 53 pg/ml (Novotny-Diermayr et al 2012).…”
Section: Pracinostat In Colorectal Cancer Therapymentioning
confidence: 96%
“…Many HDACi Okabe et al (2013) including pracinostat have shown encouraging result in AML and myelodysplastic syndrome but the desired efficacy is not achieved with these inhibitors as single agents (monotherapy) (Prebet & Vey 2011). Pracinostat has shown marvellous anticancer effect in AML models in combination therapy with pacritinib (JAK2/FLT3 kinase inhibitor) (Novotny-Diermayr et al 2012). Pacritnib an oral inhibitor has shown better patient tolerability and favourable pharmacokinetics and is currently undergoing phase-II clinical studies against myelofibrosis and lymphoma .…”
Section: Pracinostat In Colorectal Cancer Therapymentioning
confidence: 99%